Simple calculation of relative energy of C-H-N-O high explosives - Vávra, Pavel (Univerzita Pardubice, 2000)
Based on a simple decomposition equation and Kamlet's relations, a new F parameter in the form F = p (where p is the density) has been suggested for representation of relative energy of C-H-N-O high explosives. Linear relation of the F parameter to detonation enthalpy and accelerating ability of high wxplosives enabling a simple and quick evaluation of newly suggested structures of energetic materials is shown on a series of 25 individual high explosives.
Keywords: výbušiny; detonační parametry; výpočty